Early Low-Molecular-Weight Heparin Administration is Associated with Shorter Time to SARS-CoV-2 Swab Negativity. Issue 6 (August 2020) - Trunfio, Mattia; Salvador, Elena; Gaviraghi, Alberto; Audagnotto, Sabrina; Marinaro, Letizia; Motta, Ilaria; Casciaro, Riccardo; Ghisetti, Valeria; Fava, Carmen; Bonora, Stefano; Perri, Giovanni Di; Calcagno, Andrea; et al.
Background: Antiviral and immune-modulating properties of low-molecular-weight heparin (LMWH) against Coronaviridae have been reported by in vitro studies, but no in vivo evidence is yet available. We sought to know whether the timing of prophylactic doses of LMWH during the course of COVID-19 may affect the time to SARS-CoV-2 nasal-oropharyngeal swab negativization. Methods: Retrospective monocentric cross-sectional study on patients requiring sub-intensive ward admission due to first SARS-CoV-2 infection and undergoing early (EH; within 7 days from COVID-19 signs and symptoms onset) versus delayed prophylactic LMWH (DH; after 7 days). SARS-CoV-2 RNA was measured by reverse transcription real-time PCR according to scheduled time points: first swab after 2 weeks from COVID-19 onset, then at 1-week intervals until negativity. Results: Time to SARS-CoV-2 swab negativity was shorter in EH (38 patients) compared with DH (55 patients): 22 versus 37 days ( P= 0.004). The number of confirmative negative swabs in EH was significantly higher compared with DH at week 2 (21.1% versus 3.6%; P =0.017) and 4 (60.0% versus 19.6%; P <0.001). At univariate, EH differed from DH for several disease severity and clinical management parameters. Nevertheless, after accounting for the differences, Cox regression showed early LMWH administration (hazard ratio [HR] 2.91 [1.51, 5.63]; P =0.002) and higher lymphocytes nadir (HR 1.04 [1.01, 1.08]; P =0.020) as predictors of shorter time to swab negativity. Conclusions: This potential antiviral and/or immune-modulating activity of LMWH needs further in vivo confirmations by randomized controlled trials.